Ekoteologi dalam Kelas untuk Menumbuhkan Kesadaran Ekologis berbasis Ajaran Kristen pada Generasi Muda (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
This article aims to critically examine how ecotheology can be integrated into Christian Religious Education (CRE) learning in order to foster ecological awareness of the younger generation. The main problems raised are the low integration of ecological values in Christian education and the weak response of faith to the environmental crisis. This study uses a qualitative approach with library research methods, through analysis of relevant theological and pedagogical literature. The novelty of this study lies in the development of ecotheology as a pedagogical framework based on faith reflection, contextual experience, and real action in the classroom. The results of the study show that an active and transformative ecotheological learning model is able to shape the ecological character of students and strengthen spirituality that is responsible for creation. CRE teachers, schools, and churches have a strategic role in shaping a culture of faith that cares about the environment as part of a relevant and contextual Christian testimony.